Engaging kindergarten pre-service teachers in the design and implementation of STEM lessons - Evagorou, Maria (Frontiers in Education, 2024)
Engaging young students in integrated STEM early on can support them to develop their competences linked to problem solving and critical thinking. Despite the importance of STEM education in younger ages, teachers still lack the skills and competences to implement STEM in their classes. The purpose of this study is to explore how pre-service kindergarten teachers (PSTs) understand STEM education, how they design lesson plans to teach STEM and how they implement STEM in their teaching. Participants of the study were 21, 3rd and 4th year students studying to become kindergarten teachers. The participants of the current study attended a Science Methods Course for Kindergarten which is a 36 hours long course. Data collected included questionnaires, reflections, lesson plans, interviews, and classroom observations. Findings for the first research question reveal that kindergarten PSTs were not familiar with STEM education and did not have any previous experience with STEM education either as school students or during their studies at the university. Another important finding is that teachers’ views on STEM education improved after the theoretical introduction to STEM, but considerable improvement and understanding of STEM education was evident after they engaged as learners in a STEM lesson specially designed for kindergarten students. Findings from the lesson plans designed by the PSTs showed that when working in groups PSTs designed lessons which offered integration between two subjects, mainly math and science. Finally, when implementing STEM lessons PSTs had similar difficulties as when designing lessons.Additionally, PSTs reported that they did not have support from their mentors, or their mentors did not act as role models during the implementation of their designs. What this study supports is the need for teacher preparation programs to prepare kindergarten teachers in understanding what STEM is, but also supporting them in the process of designing and implementing STEM lessons. Implications from this study include the design of a teacher training course to support PSTs during their studies and in their early career, but also include mentors as part of the training course to support them to act as positive role models.